Respuesta :

gmany

Answer:

12x + 17

Step-by-step explanation:

3(4x + 5) + 2          use the distributive property: a(b + c) = ab + ac

= (3)(4x) + (3)(5) + 2

= 12x + 15 + 2         combine like terms

= 12x + (15 + 2)

= 12x + 17

Answer: 12x + 17

Step-by-step explanation:

First, distribute the 3 to the values within the parentheses.

3 * 4x = 12x

3 * 5 = 15

The expression now becomes 12x + 15 + 2. Now you can combine like terms by adding 15 and 2, since they both have no variable.

12x + 15 + 2

12x + 17

Therefore, the final answer is 12x + 17.